Evaluation of Oral Health Status Among Pregnant Women Using Oral Hygiene Index- Simplified (OHI-S) Score - Chowdhury, Sabrina Farida; Islam, Md Nazrul; Sony, Sadia Akther (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Oral health of women is often neglected during pregnancy. We need to address this issue in a developing country’s perspective,as oral healthcare is not an integral part of antenatal protocols. Objective: To evaluate the oral health status of pregnant women using Oral Hygiene Index-Simplified (OHI-S) Score as well as explore oral hygiene practice by them and conduct a mini-assessment of their knowledge of oral health. Methods: This cross-sectional, descriptive study was conducted using data by using a semi-structured questionnaire among 170 pregnant women attending an antenatal center in Dhaka city, Bangladesh,from March to August of 2018. A pre-tested semi structured questionnaire containing OHI-S indexwas used for data collection. Dental mirror and probe were used for oral hygiene assessment. Results: The mean age of the participants was 24.22±5.07 years. 140(82.4%) were found to use toothbrushes as a tooth-cleaning aid and 146(85.9%) used toothpaste as a tooth cleaning material. Among them, 132(94.3%) were found to brush at least once a day. The predominant health problems identified by clinical examination among those pregnant women were gum bleeding, mild to severe periodontitis, halitosis (bad breath) and loose teeth. The majority didnot know the safe period of dental treatment and the consequences of having poor oral health during pregnancy. The overall oral hygiene status of the maximum pregnant women was ‘Fair’ (50.6%) (OHI-S score 0-1.2), while 39.4% had ‘Poor’ oral hygiene status (OHI-S score 1.3-3.0) and only 10% had ‘Good’ oral hygiene status (OHI-S score 3.1-6.9). Conclusion: Pregnant women in Bangladesh suffer from various oral health issues during pregnancy; however, they exhibit that they do not address this issue due to lack of awareness and other factors. Hence, it is crucial to plan and implement effective oral health programmes for pregnant women all over the country. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 298-303